Clinical and genetic analysis of five Chinese patients with urea cycle disorders. Issue 7 (15th May 2020) - Zheng, Zhenzhu; Lin, Yiming; Lin, Weihua; Zhu, Lin; Jiang, Mengyi; Wang, Wenjun; Fu, Qingliu
Abstract: Background: The urea cycle plays a key role in preventing the accumulation of toxic nitrogenous waste products, including two essential enzymes: ornithine transcarbamylase (OTC) and argininosuccinate lyase (ASL). Ornithine transcarbamylase deficiency (OTCD) results from mutations in the OTC . Meanwhile, argininosuccinate lyase deficiency (ASLD) is caused by mutations in the ASL . Methods: Blood tandem mass spectrometric analysis and urea organic acidemia screening were performed on five Chinese cases, including three OTCD and two ASLD patients. Next‐generation sequencing was then used to make a definite diagnosis, and the related variants were validated by Sanger sequencing. Results: The five patients exhibited severe clinical symptoms, with abnormal biochemical analysis and amino acids profile. Genetic analysis revealed two variants [c.77G>A (p.Arg26Gln); c.116G>T (p.Gly39Val)] in the OTC, as well as two variants [c.1311T>G (p.Tyr437*); c.961T>A (p.Tyr321Asn)] in the ASL . Conservation analysis showed that the amino acids of the two novel mutations were highly conserved in different species and were predicted to be possibly damaging with several in silico prediction programs. 3D‐modeling analysis indicated that the two novel missense variants might result in modest distortions of the OTC and ASL protein structures, respectively. Conclusions: Two novel variants expand the mutational spectrums of the OTC and ASL . All the results may contribute to a better understanding of the clinical course and genetic characteristics of patients with urea cycle disorders. Abstract : Firstly, we have demonstrated five Chinese urea cycle disorder cases in detail, including three ornithine transcarbamylase deficiency patients and two argininosuccinate lyase deficiency patients. Secondly, two novel missense variants including c.116G>T in OTC and c.961T>A in ASL are found and discussed fully.